Respuesta :
In the Figure below is shown the graph of this function. We have the following function:
[tex]f(x)=x^3+2x^2-x-2[/tex]
The [tex]y-intercept[/tex] occurs when [tex]x=0[/tex], so:
[tex]f(0)=(0)^3+2(0)^2-(0)-2=-2[/tex]
Therefore, the [tex]y-intercept[/tex] is the given by the point:
[tex] \boxed{(0,-2)} [/tex]
From the figure we have three [tex]x-intercepts[/tex]:
[tex] \boxed{P_{1}(-2,0)} \\ \boxed{P_{2}(-1,0)} \\ \boxed{P_{3}(1,0)} [/tex]
So, the [tex]x-intercepts[/tex] occur when [tex]y=0[/tex]. Thus, proving this:
[tex] f(x)=x^3+2x^2-x-2 \\ \\ For \ P_{1}:\\ If \ x=-2, \ y=(-2)^3+2(-2)^2-(-2)-2=0 \\ \\ For \ P_{2}:\\ If \ x=-1, \ y=(-1)^3+2(-1)^2-(-1)-2=0 \\ \\ For \ P_{3}:\\ If \ x=1, \ y=(1)^3+2(1)^2-(1)-2=0 [/tex]
![Ver imagen danielmaduroh](https://us-static.z-dn.net/files/d55/63c587a4c873355a5c9a7e1f390957a9.png)
Answer:
Plot all four of these points on the graph (-2,0) (-1,0) (0,-2) (1,0)
Step-by-step explanation:
The other person is correct